The Effect of Work Life Balance on Employee Performance in Manufacture Companies (Case Study at PT. Gemilang Mitra Sejahtera) - Aisyah, Cita; Suryaningsih, Annisa; Putri, Dila Adinda (ADMAN: Journal of Contemporary Administration and Management, 2023)
People are a company's most important and influential asset, and that's why it needs great people. One way is to achieve work-life balance. This study aims to examine how work life balance affects employee performance at PT Gemilang Mitra Sejahtera. This research uses an associative approach with a target sampling of 50 respondents. The method for collecting data for this research is the questionnaire method. The analysis technique uses simple regression and SPSS version 26.00 software in processing the data of this study. The results of this study indicate that work-life balance is known to have a positive and significant impact on employee performance of PT Gemilang Mitra Sejahtera.